THE EFFECT OF WORKING CAPITAL, RETURN ON ASSETS AND COMPANY SIZES ON THE CREDIT AMOUNT OF SMALL AND MEDIUM MICRO BUSINESSES IN NATIONAL BANKS IN INDONESIA PRE COVID-19 - Sunaryo, Deni (Dinasti Publisher, 2020)
The research of